2016
DOI: 10.15578/jra.11.1.2016.75-83
|View full text |Cite
|
Sign up to set email alerts
|

FORMULASI PAKAN BUATAN DENGAN BAHAN BAKU RUMPUT LAUT UNTUK PERTUMBUHAN ABALON Haliotis squamata

Abstract: <p>Abalon merupakan salah satu jenis moluska laut yang memiliki potensi ekonomis untuk dikembangkan usaha budidayanya. Teknologi pembenihan abalon <em>Haliotis squamata</em> telah dikembangkan dan berhasil memproduksi benih secara massal. Selain benih, ketersediaan pakan yang sesuai sangat menentukan keberhasilan budidaya pembesaran abalon. Selain makan pakan segar berupa makroalga, abalon juga dapat menerima pakan buatan dengan baik. Penelitian ini bertujuan untuk mendapatkan formula pakan d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
3
Order By: Relevance
“…were combined with other macroalgae species, such as Eucheuma cottonii (Susanto et al, 2010), Eucheuma spinosum (Prihadi et al 2018), and Sargassum sp. evaluated as artificial compound diet (Giri et al, 2016). These studies similarly showed a positive growth response of H. squamata.…”
Section: Introductionmentioning
confidence: 69%
“…were combined with other macroalgae species, such as Eucheuma cottonii (Susanto et al, 2010), Eucheuma spinosum (Prihadi et al 2018), and Sargassum sp. evaluated as artificial compound diet (Giri et al, 2016). These studies similarly showed a positive growth response of H. squamata.…”
Section: Introductionmentioning
confidence: 69%
“…Menurut Giri et al (2016), Pada formulasi pakan buatan dengan menggunakan kombinasi tepung rumput laut juga ditambahkan tepung ikan dan tepung kedelai. Hal ini diharapkan mampu memberikan keseimbangan nutrient sesuai kebutuhan biota.…”
Section: Pendahuluanunclassified
“…To test whether food consumption is a function of temperature (Experiment 1), we produced agar-pellets containing Ulva lactuca powder (Xi'an XiaoCao Botanical Development Co., Ltd, China). Ulva lactuca is commonly used as food for abalone in hatcheries and is known to be consumed by H. squamata (Giri et al 2016;Heru Prihadi et al 2018;Yusup et al 2020). For the pellets, we mixed 7.2 g of agar powder with 100 mL of distilled water and boiled the mixture for 5 s in a microwave (800 watts).…”
Section: Herbivores and Macroalgal Foodmentioning
confidence: 99%